W.E.B Du Bois's data portraits : visualizing Black America - Du Bois, W. E. B. (William Edward Burghardt), 1868-1963.; Battle-Baptiste, Whitney; Rusert, Britt (Hudson, NY : Princeton Architectural Press, 2018)
"The colorful charts, graphs, and maps presented at the 1900 Paris Exposition by famed sociologist and black rights activist W.E.B. Du Bois offered a look behind the veil into the lives of black Americans to convey a literal and figurative representation of what Du Bois famously termed "the color line," and became the talk of the Expo. From advances in education to the lingering effects of slavery, these prophetic infographics--beautiful in design and powerful in content--make visible a wide spectrum of black experience. W.E.B. Du Bois's Data Portraits collects the complete set of graphs in full color for the first time, making their insights and innovations available to a contemporary imagination. These data portraits shaped how Du Bois thought about sociology, informing his ideas with which he set the world ablaze three years later with The Souls of Black Folk"--
American Negro at Paris, 1900 / by Aldon Morris -- The cartography of W.E.B. DuBois's color line / by Mabel O. Wilson -- Du Bois and data visualization / by Silas Munro.
boek
Keywords: Du Bois, W. E. B. -- 1868-1963.; African Americans -- Social conditions -- Charts, diagrams, etc; Information visualization; Sociology -- United States -- History; African American sociologists; Graphs